Reform und Konsolidierung des Sozialstaats: zum Stand der Willensbildung innerhalb der EKD - Strohm, Theodor (Zeitschrift für evangelische Ethik, 1996)
Over the years the consulting chambers of the EKiD deliberate in recommendations about the reform upon the system of social securitiy in modern welfare state. In the last months the Social Chamber of the EKiD draw up proposals and results of the discussion; the chamber presents a set of thesises to the Council of the EKiD. The essay gives survey of the present result of the decisions. The intention is to promote the reform and consolidation of the social state and to keep off the strategies which aim at a destruction of social security.
Online erschienen: 2014-9-9
Gesehen am 24.01.2024
Keywords: Evangelische Kirche in Deutschland; Sozialstaat